2010
DOI: 10.1111/j.1471-0528.2010.02704.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrapartum risk factors for levator trauma

Abstract: Objective To determine intrapartum risk factors associated with levator trauma as identified by ultrasound imaging.Design A prospective observational study. Population Nulliparous women (n = 488) in their first ongoing pregnancy.Methods An interview and four-dimensional translabial ultrasound was carried out between 36 and 38 weeks and again 3-4 months after delivery. Obstetric data were collected from the hospital database and/or participants' records. Main outcome measures Levator macrotrauma ('avulsion') an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
338
3
17

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 321 publications
(408 citation statements)
references
References 40 publications
(61 reference statements)
43
338
3
17
Order By: Relevance
“…5 However, the definition they used was 'a loss of continuity between muscle and pelvic side wall in all volume data sets (rest, squeeze, Valsalva)', 5 which is different from a more recent suggested definition in which TUI at maximum pelvic floor muscle contraction is used to diagnose LAM avulsion. 21 This might explain why later studies [7][8][9][10][11] using the same definition on TPUS as in our study, have found similar incidence rates of LAM avulsion. This highlights the importance of using standardising terms when research is conducted.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…5 However, the definition they used was 'a loss of continuity between muscle and pelvic side wall in all volume data sets (rest, squeeze, Valsalva)', 5 which is different from a more recent suggested definition in which TUI at maximum pelvic floor muscle contraction is used to diagnose LAM avulsion. 21 This might explain why later studies [7][8][9][10][11] using the same definition on TPUS as in our study, have found similar incidence rates of LAM avulsion. This highlights the importance of using standardising terms when research is conducted.…”
Section: Discussionsupporting
confidence: 76%
“…Nevertheless, OASIS, prolonged second stage of labour and forceps delivery will certainly put women at a high risk of LAM avulsion, which is in keeping with the literature. 6,8,10,14 It has been suggested that prediction models should only be presented when they can be clinically applicable. 24 We therefore developed clinically applicable nomograms based on our risk model, to estimate a woman's individual risk of having sustained LAM avulsion, which can be used in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We now know that the levator ani is commonly damaged in childbirth [5,6], that the use of forceps is the main risk factor [7], and that such tears and overdistension lead to excessive distensibility of the levator hiatus, the largest potential site for herniation in the human body [8]. This damage is associated with symptoms and signs of female pelvic organ prolapse [8,9], with rectal intussusception [10] and with prolapse recurrence after pelvic reconstructive surgery [11][12][13].…”
Section: Piloni Et Al Make An Important Contribution With ''Mrdefecomentioning
confidence: 99%